Let X = cost per pound and Y be the base price.
Total cost would equal base price plus weight cost = T = Y +X
For the 3 pound package the price would be the base price plus 3 times the price per pound: y + 3x
Now you have 22.85 = y +3x
For the 10 pound package you have 40 = Y + 10x
Rewrite the second equation as y = 40-10x
Replace Y in the first equation:
22.85 = 40-10x + 3x
Simplify:
22.85 = 40 - 7x
Subtract 40 from both sides:
-17.15 = -7x
Divide both sides by -7:
x = -17.15 / -7
x = 2.45
The cost per pound is $2.45
Now you can find base price:
22.85 = Y +3(2.45)
22.85 = y + 7.35
y = 22.85 - 7.35
y = $15.50
Answer for #3:
Total cost = 15.50 + 2.45X ( X = the weight of the package).
Answer for #4
Total = 15.50 + 2.45(15)
Total = 15.50 + 36.75
Total = $52.25